Realisasi Sikap Disiplin Kerja Karyawan pada PT XYZ - Athirah Delfi Arthamevia; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Jurnal Publikasi Ilmu Manajemen, 2023)
An ever-growing business organization is everyone's dream. Therefore, human resources are a vital element for a company. The purpose of this research is to determine the work discipline attitudes of employees at PT XYZ, which includes employee attendance discipline practice and disciplinary indicators applied to employees. This research uses a descriptive qualitative approach by identifying and analyzing the problems encountered. While the primary data for this research was obtained through observations, interviews, and documentation, secondary data was obtained through books, previous research, and articles related to the research. From the results of this research, it can be seen that the discipline of PT employees is relatively low, even though they can assure their responsibility to consumers; This is also considered good because employees show directly to consumers that they can be trusted to serve consumer mobility. Although it is still relatively low, it is expected from this research that company management always tries to create rules that will ensure that employees are more disciplined at work.